If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d + 4 + -2d = 2 Reorder the terms: 4 + 3d + -2d = 2 Combine like terms: 3d + -2d = 1d 4 + 1d = 2 Solving 4 + 1d = 2 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1d = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 1d = 2 + -4 1d = 2 + -4 Combine like terms: 2 + -4 = -2 1d = -2 Divide each side by '1'. d = -2 Simplifying d = -2
| -2(x+4)-3(x+5)=2x | | 5(x-2)+3(7+x)= | | -30n-30=30 | | 4a+3=3a+4 | | 8n+8=20 | | -20x+10+12x=-6 | | 3x+2y=51 | | 5y-4=3y+12 | | f(t)=-16t^2+112t | | 12-4(k+6)=24 | | 32k-32+5k=-32 | | 3n+5+4n-2= | | 8v-4v-32=8 | | -5(x+2)=7x | | 10+x/6=5 | | 30x^2-50x=0 | | -5(x+2)=7 | | -3(n-2)=3n-5n+9 | | X^3-X^2-90X=0 | | 3(n-2)=3n-5n+9 | | 3+a+-2=-3 | | 37x^3+16x^2/4x^2 | | 78-6x=21x+21 | | 12x-100=2x+90 | | 3/4y-5=11 | | 4(3n-5)=4 | | 5x+16-4x^2+6x-5= | | 7(m+3)=-4(m+3) | | 2x+x+1=10 | | 3(3g+4)=12 | | 4x=13-2x+1 | | =8m+13m |